Marginal treatment benefit in anaplastic thyroid cancer. Issue 17 (9th July 2013) - Haymart, Megan R.; Banerjee, Mousumi; Yin, Huiying; Worden, Francis; Griggs, Jennifer J.
<x xml:space="preserve">Abstract</x> BACKGROUND Because anaplastic thyroid cancer is a rare malignancy with a high mortality rate, the benefit of multimodality treatment was evaluated. METHODS Overall survival was determined in the 2742 patients captured by the National Cancer Database who were diagnosed with anaplastic thyroid cancer between 1998 and 2008. Kaplan‐Meier analysis and then Cox proportional hazard regression was performed, controlling for patient characteristics and treatment. RESULTS Only older age (adjusted hazard ratio [AHR] for ≥ 85 years = 3.43, 95% confidence interval [CI] = 2.34‐5.03; for 75‐84 years, AHR = 2.85, 95% CI = 1.97‐4.11; for 65‐74 years, AHR = 2.20, 95% CI = 1.53‐3.15; for 45‐64 years, AHR = 2.08, 95% CI = 1.47‐2.95) and omission of treatment were associated with greater mortality (omission of surgery: AHR = 1.79, 95% CI = 1.61‐1.99; omission of radiation therapy: AHR = 1.56; 95% CI = 1.41‐1.73; and omission of chemotherapy: AHR = 1.28, 95% CI = 1.15‐1.43). In subgroup analysis of patients with American Joint Committee on Cancer stage IVA, IVB, and IVC anaplastic thyroid cancer, combination therapy with surgery, radiation, and chemotherapy was associated a difference in median survival of months. CONCLUSIONS Multimodality management of anaplastic thyroid cancer results in a marginal treatment benefit. The poor overall survival of all anaplastic thyroid cancer patients, regardless of treatment, emphasizes the need for informed patients whose preferences are incorporated into treatment decision‐making. Cancer 2013;119:3133–3139. © 2013 American Cancer Society.